Experimental Effects of an Absent Crowd on Performances and Refereeing Decisions during COVID-19 - Alex Bryson; Peter Dolton; J. James Reade; Dominik Schreyer; Carl Singleton (Institute of Labor Economics (IZA), 2020)
The Covid-19 pandemic has induced worldwide natural experiments on the effects of crowds. We exploit one of these experiments currently taking place over several countries in almost identical settings: professional football matches played behind closed doors. We find large and statistically significant effects on the number of yellow cards issued by referees. Without a crowd, fewer cards were awarded to the away teams, reducing home advantage. These results have implications for the influence of social pressure and crowds on the neutrality of refereeing decisions.
Keywords: C90; D91; L83; Z20; 330; attendance; Coronavirus; COVID-19; home advantage; natural experiments; referee bias; social pressure